2017
DOI: 10.1177/1757913916679860
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic environments: current evidence of the built and food environments

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
174
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(202 citation statements)
references
References 76 publications
4
174
1
8
Order By: Relevance
“…Authorities consider it as one of the most serious public health problems of the 21 st century [1] . Although recently published guidelines recommend lifestyle modification as the initial treatment for obesity, still weight loss achieved with lifestyle intervention is modest [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Authorities consider it as one of the most serious public health problems of the 21 st century [1] . Although recently published guidelines recommend lifestyle modification as the initial treatment for obesity, still weight loss achieved with lifestyle intervention is modest [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The increased intake of processed and calorie-dense foods has led to increasing rates of overweight and obesity across countries worldwide, including the European Union [1]. While multiple factors are related to obesity, the fundamental cause of obesity is the energy imbalance between calories consumed and calories expended [1][2][3]. As suggested by the World Health Organization [1] obesity and related morbidities can be prevented through supportive environments that shape people's choices, for example by making the selection of healthier food items to be consumed the easiest choice for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…From 1980–2015, excess fat accumulation contributed to an estimated 4 million deaths through its association with cardiovascular, metabolic, cancer and other diseases, leading to a loss of 120 million disability‐adjusted life years (Afshin et al, ). An obesogenic environment, characterized by sedentary behavior and abundance of energy‐rich food, is among a very large number of potential contributors to high body mass index (BMI) at the population level (Townshend & Lake, ). However, genetic factors are also a known to affect BMI (Locke et al, ; Zaitlen et al, ), and heritability studies have indicated that 40–70% of BMI variability can be attributed to genetic factors (Zaitlen et al, ).…”
Section: Introductionmentioning
confidence: 99%